Self-medication of abortion pills and its complications: an observational study - Munshi, Kavina S.; Thaker, Rajal V.; Shah, Jagruti M.; Mewada, Bhavna N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Medical termination of pregnancy has been legalized in India since 1971. Medical abortion pill is well effective in early weeks of pregnancy. It is safe only when it is used under medical supervision. This study was carried out to analyse the complications following self-medication of abortion pills and to suggest measures to prevent such practice. Methods: This was a retrospective observational study conducted at our hospital from March 2017 to July 2017. Results: In present study 30 (75%) patients were in age group of 20-30 years. Illiterate patients were 22 (55%). Half of the patients, 20 (50%) were having three or more than three children. Majority of women 30 (75%) had consumed the abortion pills 1-10 days before coming to the hospital and 14 (35%) of patients had come with complain of excessive bleeding per vagina. Incomplete abortion was present in 32 (80%) of patients. Instrumental evacuation was required in 28 (87.5%) patients. Laparotomy for ruptured ectopic and rupture uterus was performed in 1 (2.5%) of each patient. 6 (15%) patients were severely anaemic. Transfusion of blood was required in 9 (22.5%) of patients. Conclusions: Medical abortion is effective and safe when carried out under medical supervision. Unsupervised use of medical abortion pills was associated with many complications like incomplete abortion, rupture ectopic and ruptured uterus. So, over the counter sale of medical abortion pill should be restricted.